Prisons, Prisoners and Health Care: History and Contemporary Issues - Awofeso, N.; Guggisberg, Marika (LAP Lambert Academic Publishing, 2011)
Based on their extensive professional experience in clinical services delivery, policy development, research and public health programs' implementation in prisons, the authors examine major historical features ofprisons, socio-cultural and ...